2020
DOI: 10.1016/j.ijwd.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Family impact of pemphigus disease in an Iranian population using the Family Dermatology Life Quality Index

Abstract: Background Pemphigus vulgaris (PV) is a rare but seriously disabling disorder of the skin and mucous membranes that can gravely impact the quality of life (QoL) of patients. Objective The aim of the present study was to identify how family members of patients with PV are affected by the disease. Methods A total of 118 patients with confirmed PV and one of their family members (caregivers) were enrolled in the study. To calculate disease sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A cohort study from Iran of 118 PV patients found a lower effect on sexual relationships as reported in the DLQI than other aspects of the DLQI. 2 However, this study had no control group. In another small study presented at the AAD-VMX, significantly reduced sexual function was reported in patients with PV.…”
mentioning
confidence: 84%
“…A cohort study from Iran of 118 PV patients found a lower effect on sexual relationships as reported in the DLQI than other aspects of the DLQI. 2 However, this study had no control group. In another small study presented at the AAD-VMX, significantly reduced sexual function was reported in patients with PV.…”
mentioning
confidence: 84%
“…Accordingly, pemphigus caused a remarkable impairment in the quality of life (QoL) of patients' families, associated with disease severity, mucocutaneous involvement, shorter disease duration, and male sex of patients that worsened by older age, low education, and the marital status of caregivers. 104,105 Improving knowledge and problem-solving abilities in patients and families can greatly reduce the disease burden. 106 QoL instruments and measurements Several assessment tools have been utilized to evaluate the QoL of patients with PV.…”
Section: Familial Relationshipsmentioning
confidence: 99%
“…5 Pemphigus vulgaris is one of the most serious and dangerous of these diseases and usually leads to hospitalization. 6,7 In addition to increased risk from the use of immunosuppressive medications, patients with autoimmune skin diseases are at a higher risk of infection than the general population because of their compromised skin integrity (eg, blisters, scratching). This increased risk led to concerns during the COVID-19 pandemic, especially when other predisposing factors were present.…”
Section: Introductionmentioning
confidence: 99%